Modern Aspects of Mining in Correlation Function of Risk and Environmental Sustainability. (2015) - Radosavljević, Slobodan; Dašić, Predrag; Radosavljević, Milan; Radosavljević, Jovana
Abstract: The time we live in is becoming quite demanding when it comes to the need for energy resources and final friendly energy products. Despite a highly constructive multidisciplinary scientific research effort, electricity has almost no alternative. On one hand, the need for the same in the international relations are growing and other resource potentials every day is actually decreasing. There remains the problem of how to reconcile these trends in the correlation function of the potential risks and environmental sustainability. Thus, the question remains which fewer resources are to provide more final energy for the future development of more rapid global technological processes. Decomposing questions we come to conclusions on the need of unconditional fast and high-quality redesign of existing designs or new technological processes in mining and energy. Modern technologically and qualitatively stable technological processes could provide an answer to the specific conditions in the connotation of the risks that are inevitably to be generated and the position of the overall aspects of compliance with environmental quality. This paper attempts to answer several questions that arise from the subject issues with respect to the real parameters of the demand for energy, accelerated resource exhaustion of world's resource potential and environmental sustainability in the context of the examples of techno-eco practicum in Serbia.